Genicular Nerve Block as an Effective Treatment for Knee Pain: Addressing Variability and Enhancing Meta-Analysis Reliability [Letter] - Liu J; Wen C; Xu L (Journal of Pain Research)
Jia Liu, Chao Wen, Lichen Xu Orthopedics Department, Dalian University Affiliated Xinhua Hospital, Dalian, Liaoning Province, People’s Republic of ChinaCorrespondence: Lichen Xu, Dalian University Affiliated Xinhua Hospital, 139 Yueling West Street, Ganjingzi District, Dalian City, Liaoning Province, People’s Republic of China, Email 3833979935@qq.com